Entrepreneurs’ perception on the effect of entrepreneurs’ skills towards the entrepreneurial activities at Perak Economic Planning Unit (UPEN) Perak Secretary of State's Office / Norelina Mohd Tamin - Mohd Tamin, Norelina (2011)
A cross sectional study was conduct on entrepreneurs’ perception towards entrepreneurial activities organized by Perak Economic Planning Unit, with the aim to determining the relationship and the factors that affecting the entrepreneurs’ perception towards the entrepreneurial activities such as seminar, workshop, and expo. Using a structured questionnaire, data were derived from 100 respondents using simple random sampling. Descriptive statistics was used to describe perception level and independent variable while the relationships between variable were determined by estimates structural equation models (SEM). In this study, there are three independent variable namely effect on management, effect on financial and effect on marketing meanwhile the dependent variable namely entrepreneurs’ perception. The result supported that the entrepreneurs’ perception are effect to their improvement on financial and marketing skills. This result also state that every respondent have different opinion or perception towards the entrepreneurial activities that organized by the government based on the age, gender and education level